Inequality, social mobility and redistributive preferences - Bruno Martorano; Isabel Günther (United Nations University (UNU), Maastricht Economic and Social Research Institute on Innovation and Technology (UNU-MERIT), 2023)
Previous studies on preferences for redistribution have shown that even though information on inequality changes concerns about inequality, it barely changes redistributive preferences. In an online experiment, we challenge previous results by showing US citizens a short video with facts on both inequality and social mobility and test the impact on different redistributive policies. Information on inequality of outcomes increases consensus on a more progressive tax system, whereas information on lack of equal opportunities increases participants' preferences for redistribution via fiscal spending. Both informational treatments have a stronger impact when participants also learn that higher inequality is not a necessary part of economic development. All informational treatments have a stronger impact for citizens, who underestimate the current level of inequality and trust the government.
Keywords: D31; D63; D90; H20; H40; 330; Inequality; Social Mobility; Redistribution